A Subsidiary Cell-Localized Glucose Transporter Promotes Stomatal Conductance and Photosynthesis. Issue 6 (17th April 2019) - Wang, Hai; Yan, Shijuan; Xin, Hongjia; Huang, Wenjie; Zhang, Hao; Teng, Shouzhen; Yu, Ya-Chi; Fernie, Alisdair R.; Lu, Xiaoduo; Li, Pengcheng; Li, Shengyan; Zhang, Chunyi; et al.
Abstract : Maize subsidiary cell-specific glucose transporter CST1 mediates the feedback-regulation of photosynthesis by photoassimilates at the grain-filling stage. Abstract: It has long been recognized that stomatal movement modulates CO2 availability and as a consequence the photosynthetic rate of plants, and that this process is feedback-regulated by photoassimilates. However, the genetic components and mechanisms underlying this regulatory loop remain poorly understood, especially in monocot crop species. Here, we report the cloning and functional characterization of a maize ( Zea mays ) mutant named closed stomata1 ( cst1 ). Map-based cloning of cst1 followed by confirmation with the clustered regularly interspaced short palindromic repeats (CRISPR)/ CRISPR associated protein 9 system identified the causal mutation in a Clade I Sugars Will Eventually be Exported Transporters (SWEET) family gene, which leads to the E81K mutation in the CST1 protein. CST1 encodes a functional glucose transporter expressed in subsidiary cells, and the E81K mutation strongly impairs the oligomerization and glucose transporter activity of CST1. Mutation of CST1 results in reduced stomatal opening, carbon starvation, and early senescence in leaves, suggesting that CST1 functions as a positive regulator of stomatal opening. Moreover, CST1 expression is induced by carbon starvation and suppressed by photoassimilate accumulation. Our study thus defines CST1 as a missing link in the feedback-regulation of stomatal movement and photosynthesis by photoassimilates in maize.